Why food matters: by Paul Freedman, New Haven, Yale University Press, 2021, 206 pp., ISBN 9780300253771. - Mart, Michelle (Food, Culture & Society, 2024)
"Why Food Matters" by Paul Freedman is a short and accessible book that speaks to different audiences about the cultural, social, and environmental importance of food. The author, a well-published historian, aims to overcome prejudices about food and highlights the significance of culture in understanding this subject. The book covers diverse topics such as food insecurity, class differences, religious values, cross-cultural understanding, health, gender, race, cultural rituals, and global warming, showing the unique but powerful impact of food on human culture over time. Freedman concludes by calling for accommodations between culinary Luddism and culinary modernism, emphasizing the ongoing debates within the field of food studies.